Neoteric aspects, problems and prospects of development of medical tourism in Ukraine - Flinta Natalіa (Journal of Education, Health and Sport, 2018)
The article focuses on the main issues of the current state of development of medical tourism in Ukraine. It also examines the experience of foreign countries in the field of medical tourism. One has conducted the SWOT analysis, identified the main factors determining the attractiveness of the Ukrainian medical tourism market. The article describes three main models of attracting foreign patients that are used in Ukraine. As well as determines the main aspects, problems, and potential for development. Medical tourism is another segment of the market of health tourism. Today, travel agencies indicate an increase in the number of orders for medical tourism. For a long time, this kind of tourism has been in demand among Americans and residents of Western Europe. According to Medical Insights International, since 2016, incomes from health tourism have been increasing every year by 20%, with annual market turnover reaching 40-60 billion. Europeans and Americans go abroad seeking cheap medical care (plastic operations, heart surgery, organ transplantation, and dental services are in demand). Such services are provided at the highest level not only by European clinics but also clinics in Asia, Australia, and Latin America. Given the increasing demand for passing medical examination abroad, budgets for diagnostic travel are increasing, depending on the cost of the program, which is calculated by the clinic (usually 2.5-5 thousand euros), the choice of place of residence (the diagnosis is usually outpatient), the presence of a medical interpreter, transfer, etc.